1985
DOI: 10.1111/1523-1747.ep12265365
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Function of Structural Lipids in the Water-Holding Properties of the Stratum Corneum

Abstract: In order to clarify the possible role of lipids in the water-holding property of stratum corneum, the forearm skin of 6 healthy male volunteers was treated with acetone/ether (1/1) for 1, 5, 10, and 20 min. A prolonged treatment period of 5-20 min produced a chapped and scaly appearance of the stratum corneum without any inflammatory reactions. Under these conditions, there was a marked decrease in the water-holding capacity of the stratum corneum accompanied by a considerable and selective loss of intercellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(91 citation statements)
references
References 9 publications
4
85
0
Order By: Relevance
“…Intercellular lipids in the stratum corneum have been implicated as important determinants in the water-retaining properties (1,2) and in the barrier function (3,4) of the skin. Ceramides are major constituents of intercellular lipids, comprising more than 50% of them.…”
mentioning
confidence: 99%
“…Intercellular lipids in the stratum corneum have been implicated as important determinants in the water-retaining properties (1,2) and in the barrier function (3,4) of the skin. Ceramides are major constituents of intercellular lipids, comprising more than 50% of them.…”
mentioning
confidence: 99%
“…25,26) In the oral mucosa little is known regarding the mecha nisms of water-holding properties of hyaluronic acid, which has a primary moisturizing role in sub mucosal and subcutaneous tissues. 27~29) In females with dry mouth, the level of hyaluronic acid in saliva is markedly lower than that of a normal female group.…”
Section: Discussionmentioning
confidence: 99%
“…ALT (U/L) 40 demonstrated that there is a marked decrease in ceramide level within the SC of both uninvolved and involved skin of patients with AD. Yamamoto et al 41 observed that the relative amounts of all the stratum corneum lipid classes including squalene, cholesterol esters, wax esters, triglycerides, free fatty acids, cholesterol, ceramides, cholesterol sulphate and phospholipids did not differ statistically between AD patients and controls but, a significant decrease in proportion of ceramide 1.…”
Section: Discussionmentioning
confidence: 99%